Qualitative Analysis of the Concept of Tabdzir in the Qur'an: A Study of Al-Azhar Tafsir and Its Contribution to Good Asset Management - Ummu Lathifah; Andri Nirwana; Muhammad Zakir Husein (Bulletin of Islamic Research, 2025)
This research is entitled "Qualitative Analysis of the Concept of Tabdzir in the Qur'an: A Study of Al-Azhar Tafsir and Its Contribution to Good Asset Management". The main focus of this study is to analyze how tabdzir, or waste, is interpreted in the Qur'an according to Hamka's perspective in Tafsir Al-Azhar. The research problem raised is the understanding and application of the teachings of tabdzir in the social and economic context of modern society. The research method used is a qualitative method with a literature study approach. The data was collected through the analysis of the Qur'anic text, especially the verses related to the tabdzir, as well as the interpretation given by Hamka in Tafsir Al-Azhar. This research also includes a review of relevant literature, both from books and scientific articles, to explore the context and implications of tabdzir teachings. The results of the study show that Hamka emphasized that tabdzir is a reprehensible behavior that must be avoided by Muslims. In his interpretation, Hamka associates tabdzir with social and moral responsibility, and reminds the importance of wise wealth management. He also highlighted the negative impact of waste, both on individuals and society, and called on the faithful to live simply and invest in social welfare. The significance of this research lies in its contribution to the Islamic understanding of asset management and ethical financial behavior. By analyzing tabdzir in the context of Tafsir Al-Azhar, this research provides useful insights for society in facing the challenges of modern lifestyles, as well as strengthening awareness of the importance of managing wealth as a mandate from Allah.